Offender Families as Victims and Their Role in Offender Reintegration - Pfeiffer, Catherine Warren (2018)
Ninety-five percent of all offenders are released, most of whom return to family members who have suffered greatly from their loved one's criminal behavior; yet, research on their victimization and trauma is rare. Additionally, families anticipate a role in the offender's reintegration; however, little research has explored their own recovery and insights on their reintegrative efforts. This qualitative phenomenological study sought to discover a deeper understanding of the lived experiences of 13 offender family members in Texas. Participants were recruited through community organizations and selected through a purposeful sampling strategy to ensure diversity. The data were collected through screening and face-to-face interviews and analyzed through iterative hand coding and thematic development, supported by secondary coding review and participant verification. Concepts explored included victimization within a trauma-informed environment, whereby support systems understand the impact of trauma on individuals and reintegration within a restorative justice model, which aims to restore individual and community trust. Results found that participants voiced consistent themes of victimization, presented effective coping mechanisms and overall continued relationships with friends, family members, and the community. Findings also showed that participants anticipated roles of both emotional and instrumental support and reported an interest in their involvement with a restorative justice option for the offender upon his reentry. The findings draw no definitive conclusions on the degree of family member victimization but do promote social change for developing policies that collaboratively engage family members within the judicial and reentry process to reduce recidivism